2021
DOI: 10.1088/1755-1315/738/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pandemic COVID-19 on the Implementation of Construction Contracts

Abstract: The COVID 19 pandemic has affected various sectors in the world, including the construction sector in Indonesia. The biggest impact is the impact on the health sector and the economy. The government budget for the construction sector has been cut very significantly, which has a negative impact on stakeholders, especially causing financial problems for business actors in construction. In this study, the identification of the impact of the COVID 19 pandemic was carried out on the construction sector, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…A significant part of the obtained results is consistent with the experiences of organizations from other sectors of the economy (particularly commercial businesses). This mainly concerns the significant role of risk analysis in project management under crisis conditions [117,118], the negative impact of the COVID-19 pandemic on the performance of implemented projects [65][66][67][68] and the significant impact of the pandemic on the organization of work of project teams, particularly including the introduction of rules for remote work [74,78,119]. Regarding the anticipated changes in the area of project management, the results correspond directly with conclusions concerning the increased importance of risk management [86], and the progress of virtualization and digitization in project management in the future [89,90], in addition to H4.0 adaptation in terms of building resilience of healthcare organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant part of the obtained results is consistent with the experiences of organizations from other sectors of the economy (particularly commercial businesses). This mainly concerns the significant role of risk analysis in project management under crisis conditions [117,118], the negative impact of the COVID-19 pandemic on the performance of implemented projects [65][66][67][68] and the significant impact of the pandemic on the organization of work of project teams, particularly including the introduction of rules for remote work [74,78,119]. Regarding the anticipated changes in the area of project management, the results correspond directly with conclusions concerning the increased importance of risk management [86], and the progress of virtualization and digitization in project management in the future [89,90], in addition to H4.0 adaptation in terms of building resilience of healthcare organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic and unexpected materialization of multiple risks related to the COVID-19 pandemic may, in many cases, have a negative impact on the performance of the implemented projects. This can be seen, in particular, in the construction industry [63][64][65], where the COVID-19 pandemic had a negative impact on the timely implementation of construction projects. The results of other research indicate that the pandemic also had a negative impact of the performance of projects in the energy sector [66], infrastructure [67] or crowd-funding projects [68].…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Based on the interviews with several informants, it was stated that the COVID-19 pandemic caused a considerable impact, especially in projects that caused some projects to be hampered or withdrawn due to worker restrictions. Following research conducted by Larasati et al (2021), it was stated that the COVID-19 pandemic caused more than 50% of construction contracts to change, the most significant change in the implementation time clause. Some stakeholders responded to the pandemic by reducing the on-site workforce, automatically impacting turnaround time.…”
Section: Impact Of Covid-19 On the Companymentioning
confidence: 99%
“…Their results showed that the novelty and criticality of the pandemic improved several dimensions of OCB or construction employees, such as their compliance and dedication. Larasati et al (2021) developed a questionnaire to investigate the impact of the COVID-19 pandemic on the implementation of construction contracts. Their results showed that the pandemic had a significant impact on the implementation of construction contracts, especially at the planning stage of projects.…”
Section: Literature Reviewmentioning
confidence: 99%